2012
DOI: 10.1007/s11606-012-2063-z
|View full text |Cite
|
Sign up to set email alerts
|

Empathy Training for Resident Physicians: A Randomized Controlled Trial of a Neuroscience-Informed Curriculum

Abstract: A brief intervention grounded in the neurobiology of empathy significantly improved physician empathy as rated by patients, suggesting that the quality of care in medicine could be improved by integrating the neuroscience of empathy into medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
262
3
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(298 citation statements)
references
References 37 publications
6
262
3
7
Order By: Relevance
“…Targeted physician communication training has been shown to make a significant difference in physician empathic expression during patient interactions demonstrated by both outside observer measures of global ratings and hierarchical ratings of physician empathic behavior [19]. A randomized controlled trial of an empathy training intervention grounded in neuroscience found that physician empathy as rated by patients significantly improved [20]. Computer-based training programs have been shown to improve doctors' empathic response to patients' expressions of negative emotions [21].…”
Section: Discussionmentioning
confidence: 99%
“…Targeted physician communication training has been shown to make a significant difference in physician empathic expression during patient interactions demonstrated by both outside observer measures of global ratings and hierarchical ratings of physician empathic behavior [19]. A randomized controlled trial of an empathy training intervention grounded in neuroscience found that physician empathy as rated by patients significantly improved [20]. Computer-based training programs have been shown to improve doctors' empathic response to patients' expressions of negative emotions [21].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Riess et al (2012), trainee participants from two institutions were randomly assigned in a 1:1 allocation ratio to a training intervention group or a control group (training as usual). A computer-generated number sequence determined allocation and participants and patient raters were both blinded to the randomisation.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
“…Using existing methodology, findings can be aggregated without masking the impact of underlying mechanisms, as long as these potential mechanisms are identified in advance. Relational factors that can be measured empirically and in which therapists can be trained can be tested in randomized controlled trials, as has recently been done with empathy in the context of physician training [7,8]. Such trials could then be aggregated in meta-analyses.…”
Section: Specific Versus Relational Factors In Addiction Treatment: Tmentioning
confidence: 99%